Are flight staffs at higher risk for breast cancer? - K Ziyari; O Rahmani; R Eslami (فصلنامه ابن سینا)
Background: Several studies have shown that there is an increased risk of breast cancer among flight attendants. However, the results of epidemiological studies have not been consistent with this issue. We conducted a brief overview on existing studies on the presence of breast cancer in flight staffs. Materials and methods: A review of databases such as PubMed, Scopus, Embase, Google,Scholar, and ... for related observational studies was undertaken until October 2017. The following keywords were used individually and in all possible various combinations: “breast cancer”, “flight staffs”, and “aerospace medicine”. Results:  The incidence of breast cancer among female flight attendants is higher than normal population. However, no study showed a high mortality rate from breast cancer in this group. Night-time rhythm disturbances due to night shift and changes in time zones which both lead to melatonin disturbances and also exposure to cosmic rays were likely to increase this risk. The results did not differ significantly from year of publication, geographical area, and study quality. Conclusion: Several observational studies and also meta-analyzes showed that the flight group had a higher risk than the normal population for breast cancer. Studies with larger sample sizes are required based on the different population and taking into account all the involved factors.